Novel lecithin-integrated liquid crystalline nanogels for enhanced cutaneous targeting of terconazole: development, in vitro and in vivo studies - Elnaggar YSR (Dove Medical Press, 2016)
Yosra SR Elnaggar,1,2 Sara M Talaat,1 Mohammed Bahey-El-Din,3 Ossama Y Abdallah1 1Department of Pharmaceutics, Faculty of Pharmacy, Alexandria University, 2Department of Pharmaceutics, Faculty of Pharmacy and Drug Manufacturing, Pharos University in Alexandria, 3Department of Microbiology and Immunology, Faculty of Pharmacy, Alexandria University, Alexandria, Egypt Abstract: Terconazole (Tr) is the first marketed, most active triazole for vaginal candidiasis. Owing to poor skin permeation and challenging physicochemical properties, Tr was not employed for the treatment of cutaneous candidiasis. This is the first study to investigate the relevance of novel lecithin-integrated liquid crystalline nano-organogels (LCGs) to improve physicochemical characteristics of Tr in order to enable its dermal application in skin candidiasis. Ternary phase diagram was constructed using lecithin/capryol 90/water to identify the region of liquid crystalline organogel. The selected organogel possessed promising physicochemical characteristics based on particle size, rheological behavior, pH, loading efficiency, and in vitro antifungal activity. Microstructure of the selected organogel was confirmed by polarized light microscopy and transmission electron microscopy. Ex vivo and in vivo skin permeation studies revealed a significant 4.7- and 2.7-fold increase in the permeability of Tr-loaded LCG when compared to conventional hydrogel. Moreover, acute irritation study indicated safety and compatibility of liquid crystalline organogel to the skin. The in vivo antifungal activity confirmed the superiority of LCG over the conventional hydrogel for the eradication of Candida infection. Overall, lecithin-based liquid crystalline organogel confirmed its potential as an interesting dermal nanocarrier for skin targeting purpose. Keywords: terconazole, liquid crystalline, organogel, skin targeting, skin mycosis